Certain Investigations on Edge Fed Microstrip Patch Array Antenna for WiMAX Applications - Ramya, M.; Parthipan, V.; Yogadeepan, M. (Asian Journal of Electrical Sciences, 2015)
Recently, a new wireless technology, i.e., Worldwide interoperability for Microwave Access (WiMAX), has been demonstrated to have its strong potential to provide a very high speed of broadband services. By simultaneously using multiple antennas at transmitter and receiver sites, these systems exploit the spatial dimension of the propagation channel. The development of such antennas includes the design of array antenna, optimizing the array antenna parameters and thereby increasing its performance. This paper mainly focuses on design of single microstrip patch antennae and linear array configurations by optimizing the various antenna parameters such as directivity, gain, Mutual coupling and beamwidth etc., Microstrip array antennae designed and simulated using IE3D for WiMAX application operating at 2.4GHz and the same configurations are also optimized and analyzed. In this analysis, upon comparing the parameters such as gain, directivity, return loss and 3-dB beamwidth quantitatively it is proposed that the linear array promises very narrow beamwidth with optimized gain.